A compact frequency reconfigurable beam switching antenna based on a single‐layer FSS - Guang Li; Yangyang Ye; Fushun Zhang (IET Circuits, Devices and Systems)
Abstract A compact frequency reconfigurable beam switching antenna based on a single‐layer frequency selective face (FSS) is proposed in this paper. The proposed antenna consists of a dual‐band dipole antenna and a single‐layer FSS with hexagonally arrangement. The omnidirectional radiation pattern of the dipole antenna designed as a radiation source and surrounded by the FSS can be converted into directional radiation pattern sweeping along the entire azimuthal plane at two single frequency of 2.4 or 5 GHz. The frequency selection is achieved by controlling the diode state of the FSS unit, and the beam switching is realised by a specific combination of electromagnetic wave reflection or transmission from the hexagonal FSS. The novelty lies in applying the hexagonal arrangement to a dual single‐frequency single‐layer FSS unit. This will not destroy the reflection or transmission characteristics of the FSS unit, but also contribute to reduce the antenna size and achieve a low cost. To validate the design, a prototype is fabricated and measured. The single‐layer FSS antenna with a volume of 57 mm × 57 mm × 58.5 mm can be scanned in 12 steps along the azimuth plane at 2.4 and 5 GHz, respectively.